A Dedication Of Cooperatives In Building The Indonesian Economy - Muhammad Saleh Rizkian; Devi Purnama Sari; Hilda Elsera Br Sembiring (Jurnal Ekonomi, 2024)
This study aims to analyze the impact or contribution of cooperatives in building the Indonesian economy. Cooperatives as institutions that prioritize the principles of togetherness and economic democracy have great potential in empowering communities to build the Indonesian economy. The strategic role of cooperatives in helping communities that are ultimately able to become one of the key factors in realizing the vision of Golden Indonesia in 2045. This study uses a quantitative descriptive method using secondary data sourced from the Central Statistics Agency and the Ministry of Cooperatives and SMEs. The method of data collection is through a literature review. The results of the study show that cooperatives in Indonesia have consistently experienced growth over time wherein 2000 the number of active cooperatives was 88,930 units and in 2021 it increased to 127,846 units or an increase of 43.76% in a period of 22 years, then the composition of cooperative capital in Indonesia also consistently experienced significant growth. The growth in the number of units and capital structure of the cooperative shows that cooperatives still exist in Indonesian society as one of the people's economic institutions. The strategic role of cooperatives as one of the driving forces of the national economy can also be seen from how much influence cooperatives have on the national gross domestic product (GDP) in the last 5 years which has continued to grow. The journey of the national economy has a very close relationship with the people's economic institutions called cooperatives. Cooperatives have been able to answer the challenges of uncertain conditions into controlled conditions, until now, for 77 years cooperatives have given color or dedication to the Indonesian economy and it is hoped that the strategic role of cooperatives can continue to be improved.